The Evolution of Islamic Law of Nations and the Modern International Order - Mashood A. Baderin (International Institute of Islamic Thought, 2000)
As traditionally understood, the Islamic State and the Shari’ah have been seen inimical to contemporary international law, membership in the United Nations Organization, and the Universal Declaration of Human Rights. Hardline advocates of the Shari’ah argue that the institution of nation-state and modem internationalism are hostile to the Islamic polity. The position taken here, however, argues quite the opposite. Through looking at the theory and practice of Islamic Law, it is claimed that the Islamic Law of Nations is evolutionary in character. The participation of Muslim nations in the modem international order is not antagonistic to the principles of Shari’ah. Islamic law can accommodate the modern international order on the basis of cooperation and peaceful coexistence.